“A Vida Pela Flor” para clarineta e banda de Joaquim Antônio Langsdorf Naegele: uma proposta interpretativa - Araújo, Daniel Souza de (2013)
This work is a proposed interpretative work for clarinet and Brazilian music band concert entitled "A Vida pela Flor" written by the conductor and composer Antônio Joaquim Langsdorf Naegele. Naegele had three of his compositions published by FUNARTE. The music "A Vida pela Flor" is atypical for making use of a fantasy within the context of repertoire for band. Its structure is divided into: Introduction, 1st theme with two variations, 2nd theme with five variations and codetta, differing from the simple structure of most works focused for band, like march, polkas, mazurkas, waltzes, among others. "A Vida pela Flor" stands out for its virtuosity, if taken into account that at the time was run by an instrument with fewer technical resources (Müller System - 13 keys), a remarkable fact. The piece has simple sentences, but with great richness of technique: scales, arpeggios, leaps between different registers of the clarinet, and variation of articulation. Such sentences, or fragments of them, are comparable to those found in the exercises in the "Complete Method for Clarinet" by Elenore Hyacinthe Klosé (1808-1880) which makes us believe that divulging this work will enrich the clarinet repertoire. Knowing that this work is not well divulged among teachers, composers and clarinetists, this study may arise interest to demonstrate the cultural richness that it may bring to our context.